Q methodology and the sociotechnical perspective - Muriel Frank; Vanessa Kohn; Roland Holten (Information Systems and e-Business Management, 2024)
Abstract When studying information systems (IS) phenomena, scholars increasingly aim to take a socio-technical approach. This means that instead of focusing exclusively on the technical side, they also study them from a human perspective. An underrecognized yet powerful tool for examining the opinions and attitudes of individuals is the Q methodology because it makes subjective viewpoints on IS phenomena objectively measurable. Despite its benefits and wide application in other disciplines, the use of Q methodology in top IS journals is still rare. Based on a systematic literature review, this article explores the potential and fit of Q methodology within the sociotechnical systems framework. This analysis leads to two main insights. First, Q methodology enables the integration of the social and the technical component as well as instrumental and humanistic outcomes. Second, this qualiquantilogical technique enriches the understanding of IS phenomena by objectifying the approach to exploring subjective viewpoints. Thus, our work highlights the potential of the method for conducting IS research. And it also provides clear guidelines on how to use the method to uncover new patterns inherent in the data being studied.
Keywords: 330; Q methodology; Systematic literature review; Sociotechnical perspective; STS framework